Coworkers, Networks, and Job-Search Outcomes among Displaced Workers. (January 2021) - Saygin, Perihan Ozge; Weber, Andrea; Weynandt, Michèle A.
This article examines the mechanisms by which social networks affect the labor market outcomes of displaced workers. The authors draw on administrative records for the universe of private-sector employment in Austria to identify work-related networks among former coworkers. They analyze the importance of social networks for both job seekers and hiring firms. For job seekers, results indicate that having a high share of former coworkers who are currently employed in expanding firms improves job-finding success. For firms seeking to hire new employees, the authors find that a firm is twice as likely to hire a displaced worker with a former-coworker link to one of their current employees than to hire a worker displaced from the same closing firm but without a link. These results suggest that information about job opportunities and demand-side conditions is transmitted in work-related networks between workers and firms.